PEMENUHAN HAK REKREASIONAL TERHADAP NARAPIDANA ANAK DI LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) KELAS I MEDAN - Emanuel Lukas Sanga Ruing (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This journal discusses and analyzes the duties and functions of the Class I Medan Special Child Development Institute (LPKA) in providing guidance and fulfillment of children's rights while in LPKA, one of which is about the fulfillment of recreational rights for students. Recreational activities given to children while in LPKA have a significant impact, namely being able to reduce stress levels in children during the coaching period. In Law No. 11 of 2012 concerning the Juvenile Criminal Justice System in article 3 states that every child in the criminal justice process has the right to carry out recreational activities, but in fact it was found that the Medan Class I LPKA has not carried out the fulfillment of recreational rights optimally. The research method used in this study is a qualitative method and data collection through interviews, observation, documentation and library research. The results show that the fulfillment of recreational rights has not run optimally. It is not clearly regulated how the mechanism for granting recreational rights is and only relies on the policy of the head of the LPKA. The inhibiting factors for the implementation of recreational activities are as follows: limited budget, inadequate facilities, low enthusiasm of students.